Eksistensi Putusan Mahkamah Konstitusi Pasca Disahkannya Undang-Undang Penetapan Perpu Cipta Kerja - Suhardin, Yohanes; Flora, Henny Saida (JURNAL USM LAW REVIEW, 2023)
This study aims at analyzing the existence of Constitutional Court Ruling No. 91/PUU-XVIII/2020 (Job Creation MK Decision) after Law No. 6 of 2023 concerning Job Creation. This research is a normative legal research by prioritizing case approaches, concepts, and legislation. The results of the study confirmed that the existence of the Job Creation MK Decision after the passage of the Job Creation Law was as if the Job Creation MK Decision was between "there and not". It is said that there is because it is used as a juridical basis in the Job Creation Law, however substantively the Decision of the Job Creation MK, especially the constitutional order to substantively improve the Job Creation Law by involving meaningful community participation, has not been implemented. Because, the government (in this case the President) actually uses the Job Creation Law instrument which substantively denies the Job Creation MK Decision. The legal implications of the Job Creation MK Decision after the Job Creation Law was passed is that the Job Creation Law has actually violated the substance of the Job Creation MK Decision. It can be seen that the Job Creation MK Decision orients the reformulation of the Job Creation Law through meaningful participation involving all components of society. The existence of disobedience to the Job Creation Law against the Decision of the Job Creation MK has the potential to cause a phenomenon of disregard for the constitution (constitutional disobedience). Therefore, in the future it is necessary to formulate the forms and types of sanctions against the Constitutional Court's Decision and also be oriented to the Constitutional Court being able to review a Law or UU that contradicts the Constitutional Court's Decision. Penelitian ini bertujuan pada analisis atas eksistensi Putusan Mahkamah Konstitusi No. 91/PUU-XVIII/2020 (Putusan MK Cipta Kerja) pasca disahkannya UU No. 6 Tahun 2023 tentang Cipta Kerja. Penelitian ini merupakan penelitian hukum normatif dengan mengedepankan pendekatan kasus, konsep, dan perundang-undangan. Hasil penelitian menegaskan bahwa eksistensi Putusan MK Cipta Kerja pasca disahkannya UU Cipta Kerja seolah-olah Putusan MK Cipta Kerja adalah antara “ada dan tiada”. Dikatakan ada karena dijadikan landasan yuridis dalam UU Cipta Kerja akan tetapi secara substantif Putusan MK Cipta Kerja khususnya perintah konstitusional untuk memperbaiki UU Cipta Kerja secara substantif dengan melibatkan partisipasi masyarakat secara bermakna, justru tidak dilaksanakan. Pemerintah (dalam hal ini Presiden) justru menggunakan instrumen UU Cipta Kerja yang secara substantif mengingkari Putusan MK Cipta Kerja. Implikasi hukum Putusan MK Cipta Kerja pasca disahkannya UU Cipta Kerja adalah bahwa UU Cipta Kerja sejatinya telah melanggar substansi dari Putusan MK Cipta Kerja. Hal ini dapat dilihat bahwa Putusan MK Cipta Kerja mengorientasikan perumusan ulang UU Cipta Kerja melalui partisipasi yang bermakna dengan melibatkan segenap komponen masyarakat. Adanya ketidaktaatan UU Cipta Kerja terhadap Putusan MK Cipta Kerja berpotensi membuat adanya fenomena pengabaian terhadap konstitusi (constitutional disobedience). Oleh karena itu, ke depan perlu diformulasikan bentuk dan jenis sanksi terhadap Putusan MK serta diorientasikan pula MK dapat melakukan pengujian terhadap suatu undang-undang atau UU yang bertentangan dengan Putusan MK.